Electrophotographic photoreceptor, and process cartridge and image forming apparatus including the same
By integrating a specific electron transporting material and silica filler into the photoreceptor's photosensitive layer, the photoreceptor achieves enhanced light resistance and abrasion resistance, ensuring stable electrical characteristics and high-quality images even under external light exposure.
Patent Information
- Application Number
- JP2023097106
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-13
- Publication Date
- 2024-12-25
AI Technical Summary
Existing electrophotographic photoreceptors suffer from light resistance and abrasion issues, leading to deteriorated electrical characteristics and poor image quality when exposed to external light during maintenance or paper jam removal, despite the addition of electron transport materials for light resistance, which can trap charges and reduce wear resistance.
Incorporating a specific electron transporting material with a silica filler into the photosensitive layer, balancing their content and average primary particle diameter to satisfy the relationship 0.12 < w/(d×x) < 0.54, where w is the silica filler content, x is the electron transport substance content, and d is the average primary particle diameter, enhances light resistance and potential stability.
The solution provides electrophotographic photoreceptors with improved light resistance, abrasion resistance, and consistent image quality by effectively blocking external light and promoting charge recombination, maintaining electrical stability during repeated use.
Smart Images

Figure 2024178735000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an electrophotographic photoreceptor, and a process cartridge and an image forming apparatus including the same. [Background technology]
[0002] Electrophotographic image forming apparatuses (electrophotographic apparatuses) that form images using electrophotographic technology are widely used in copiers, printers, facsimile machines, and the like. The electrophotographic photoreceptor (hereinafter also referred to as "photoreceptor") used in this electrophotographic process is configured by laminating a photosensitive layer containing a photoconductive material on a substrate, and photoreceptors having a photosensitive layer whose main component is an organic photoconductive material (hereinafter also referred to as "organic photoreceptor") are widely used.
[0003] A drawback of photoconductors is their light resistance. During normal use, photoconductors are not exposed to external light such as fluorescent lights, but they are exposed to external light when performing maintenance on replacement parts such as the photoconductor and peripheral components, or when paper is removed due to a paper jam inside the machine. If the photoconductor is exposed to external light, it can be severely damaged, causing problems in the image. As a means for overcoming this drawback, a method of adding a specific electron transport material (ETM) to the photosensitive layer has been proposed (for example, JP 2010-164639 A: Patent Document 1, International Publication No. WO2018 / 150693: Patent Document 2). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2010-164639 A [Patent Document 2] International Publication No. WO2018 / 150693 Summary of the Invention [Problem to be solved by the invention]
[0005] In any of the above-mentioned prior arts, when an electron transport material is added to a photosensitive layer in an amount sufficient to obtain sufficient light resistance, the electron transport material itself becomes a trap, resulting in problems such as deterioration of the stability of the potential during repeated application, and an increase in the proportion of low-molecular-weight components in the photosensitive layer, which makes it impossible to obtain sufficient abrasion resistance. Therefore, an object of the present disclosure is to provide an electrophotographic photoreceptor that has excellent light resistance and abrasion resistance, does not deteriorate in electrical characteristics during repeated use, and can continuously provide good image quality, and a process cartridge and an image forming apparatus equipped with the same. [Means for solving the problem]
[0006] As a result of intensive research into solving the above problems, the inventors have found that the above problems can be solved by incorporating an electron transport material having a specific structure and a silica filler in a photosensitive layer, and have thus completed the present invention.
[0007] Thus, according to the present disclosure, there is provided an electrophotographic photoreceptor having at least a photosensitive layer on a conductive support, The photosensitive layer comprises a silica filler and a compound represented by the general formula (I): [ka]
[0008] (In the formula, R a and R b are the same or different and represent a hydrogen atom, a halogen atom, a cyano group, a nitro group, a hydroxyl group, an alkyl group having 1 to 12 carbon atoms, an alkoxy group having 1 to 12 carbon atoms, an aryl group which may have a substituent, a heterocyclic group which may have a substituent, an ester group, a cycloalkyl group, an aralkyl group which may have a substituent, an allyl group, an amide group, an amino group, an acyl group, an alkenyl group, an alkynyl group, a carboxyl group, a carbonyl group, a carboxylic acid group, or a halogenated alkyl group, and the substituent is a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, a hydroxyl group, a cyano group, an amino group, a nitro group, or a halogenated alkyl group. The electron transport material is represented by
[0009] When the content of the silica filler relative to the total solid content of the photosensitive layer is w (mass%), the average primary particle diameter of the silica filler is d (nm), and the content of the electron transport material relative to the total solid content of the photosensitive layer is x (mass%), 0.12 <w / (d×x)<0.54 The electrophotographic photoreceptor is characterized in that it satisfies the following relationship.
[0010] In addition, according to the present disclosure, there is provided a process cartridge comprising the above-mentioned electrophotographic photosensitive member, and at least one selected from a charging means for charging the electrophotographic photosensitive member, a developing means for developing an electrostatic latent image formed by exposure to light to form a toner image, and a cleaning means for removing toner remaining on the electrophotographic photosensitive member.
[0011] Furthermore, according to the present disclosure, there is provided an image forming apparatus comprising at least the above-mentioned electrophotographic photoreceptor, a charging unit for charging the electrophotographic photoreceptor, an exposure unit for exposing the charged electrophotographic photoreceptor to light to form an electrostatic latent image, a developing unit for developing the electrostatic latent image to form a toner image, and a transfer unit for transferring the toner image onto a recording medium. Effect of the Invention
[0012] According to the present disclosure, it is possible to provide an electrophotographic photoreceptor that has excellent light resistance and abrasion resistance, does not deteriorate in electrical properties during repeated use, and can continuously provide good image quality, as well as a process cartridge and an image forming apparatus equipped with the same. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a schematic cross-sectional view showing the configuration of a main part of a photoreceptor (laminated photoreceptor) 1 according to the present disclosure. [Diagram 2] 1 is a schematic side view showing a configuration of a main part of an image forming apparatus 100 according to the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The photoreceptor of the present disclosure is an electrophotographic photoreceptor having at least a photosensitive layer on a conductive support, the photosensitive layer contains a silica filler and an electron transport material represented by general formula (I) described below, When the content of the silica filler relative to the total solid content of the photosensitive layer is w (mass%), the average primary particle diameter of the silica filler is d (nm), and the content of the electron transport material relative to the total solid content of the photosensitive layer is x (mass%), 0.12 <w / (d×x)<0.54 The above relationship is satisfied. The "content of the silica filler and the electron transport material relative to the total solid components of the photosensitive layer" means the content of the silica filler and the electron transport material relative to the total solid components in the photosensitive layer containing the silica filler and the electron transport material, respectively. Therefore, when the photosensitive layer described later is a laminated type photosensitive layer of a charge generation layer and a charge transport layer, the content of the silica filler and the electron transport material relative to the total solid components in the charge transport layer containing the silica filler and the electron transport material, respectively, means the content of the silica filler and the electron transport material relative to the total solid components in the charge transport layer containing the silica filler and the electron transport material, respectively. In this specification, a numerical range "A to B" means "greater than or equal to A and less than or equal to B." For example, when the variable is "x," it means "A≦x≦B."
[0015] Below, the constituent features that characterize the photoreceptor of the present disclosure will be described, followed by a description of (1) the photoreceptor, (2) the process cartridge, and (3) the image forming apparatus. It should be noted that the embodiments and examples described below are merely specific examples of the present invention, and the present invention is not limited thereto.
[0016] <Relationship between the content of electron transport material and the average primary particle size and content of silica filler> Damage to photoreceptors caused by external light from fluorescent lights, LEDs, etc. occurs when the external light penetrates the charge transport layer and acts on the charge generating material, generating charge traps. When the photosensitive layer contains silica filler, memory (charge) tends to be generated easily when exposed to external light, and light resistance tends to deteriorate. The reason for this is unclear, but it is thought that when the photosensitive layer contains fine particles such as silica that easily become negatively charged, the excess carriers generated in the charge generating layer when exposed to light tend to become stable.
[0017] In laminated photoreceptors, the light resistance of the photoreceptor tends to worsen. When the charge transport layer contains silica filler, the surface area of the interface between the charge transport layer and the charge generation layer increases. As a result, the contact area between the charge transport layer and the charge generation layer increases, and the rate of penetration of the hole transport material into the charge generation layer increases, causing the stacking structure of the charge generation material, which is originally arranged regularly, to become disordered. As a result, traps generated when exposed to light tend to stabilize without recombining, resulting in poor light resistance. On the other hand, the charge exchange between the layers is smooth, making it difficult for the residual potential to increase, and the potential stability is good. The smaller the average primary particle size of the silica filler and the higher the silica filler content, the greater the contact area, which promotes both advantages and disadvantages.
[0018] The electron transport material has a function of effectively blocking the action of the light wavelength component of external light on the charge generating material and a function of promoting recovery from damage caused by exposure to light. In the present disclosure, the electron transport material absorbs external light to suppress the generation of charge traps. In addition, when traps are generated, the electron transport ability promotes recombination of the charge traps and promotes recovery from damage. The more the electron transport material is added, the better the light resistance becomes, but the electron transport material itself can become a trap, which can cause deterioration of electrical properties.
[0019] As described above, since the content of the electron transport material, the content of the silica filler, and its average primary particle diameter each have a great influence on light resistance and potential stability, the balance among them is important. When the content of the electron transport material with respect to the total solid content of the photosensitive layer is x (mass %), the content of the silica filler with respect to the total solid content of the photosensitive layer is w (mass %), and the average primary particle diameter of the silica filler is d (nm), a photosensitive member having excellent light resistance and potential stability during repeated use can be obtained when the relationship of 0.12 < w / (d×x) < 0.54 is satisfied. When w / (d×x) is 0.12 or less, the w value may be too large with respect to the (d×x) value, and thus the potential stability may deteriorate. On the other hand, when w / (d×x) is 0.54 or more, the w value may be too small with respect to the (d×x) value, and thus the desired light resistance and recoverability from light damage may not be obtained. Preferably, 0.15 < w / (d×x) < 0.50, and more preferably 0.20 < w / (d×x) < 0.43.
[0020] <Electron transport material> Since a general fluorescent lamp has a strong light wavelength component near 550 nm, these light wavelength components act on the charge generation material to generate charge traps. On the other hand, since the light wavelength component near 600 nm is used in an LED or a laser beam for exposing the photosensitive member to form an electrostatic latent image and an LED for discharging the surface charges remaining on the photosensitive member, if the light of this wavelength is blocked, the residual potential will increase and the repeated potential stability cannot be maintained. Therefore, the electron transport material preferably has a maximum absorption wavelength λ in the range of 515 to 560 nm. max A more preferable wavelength range is 525 to 555 nm.
[0021] The electron transport material of the present disclosure has the general formula (I): [Chemical formula]
[0022] (In the formula, R a and R bare the same or different and represent a hydrogen atom, a halogen atom, a cyano group, a nitro group, a hydroxyl group, an alkyl group having 1 to 12 carbon atoms, an alkoxy group having 1 to 12 carbon atoms, an aryl group which may have a substituent, a heterocyclic group which may have a substituent, an ester group, a cycloalkyl group, an aralkyl group which may have a substituent, an allyl group, an amide group, an amino group, an acyl group, an alkenyl group, an alkynyl group, a carboxyl group, a carbonyl group, a carboxylic acid group, or a halogenated alkyl group, and the substituent is a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, a hydroxyl group, a cyano group, an amino group, a nitro group, or a halogenated alkyl group. It is expressed as:
[0023] The substituent R in the general formula (I) a and R b The substituents which may be present will be described below. Examples of the alkyl group include alkyl groups having 1 to 6 carbon atoms, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, and n-hexyl, and alkyl groups having 7 to 12 carbon atoms, such as n-heptyl, n-octyl, n-nonyl, n-decyl, n-undecyl, and n-dodecyl. Examples of the alkoxy group include alkoxy groups having 1 to 6 carbon atoms, such as methoxy, ethoxy, n-propoxy, isopropoxy, tert-butoxy, n-pentyloxy, and n-hexyloxy, and alkoxy groups having 7 to 12 carbon atoms, such as n-hexyloxy, n-octyloxy, n-nonyloxy, n-decyloxy, n-undecyloxy, and n-dodecyloxy. Examples of the aryl group include phenyl, naphthyl, anthryl, phenanthryl, fluorenyl, biphenylyl, and o-terphenyl.
[0024] Heterocyclic groups include, for example, pyridyl, indolyl, carbazole, thiophene, and the like. Cycloalkyl groups include, for example, cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, and the like. Examples of the acyl group include acetyl, propanoyl, and benzyl. Aralkyl groups include, for example, benzyl, phenethyl, benzhydryl, trityl, and the like. Alkenyl groups include, for example, vinyl, propenyl, allyl, butenyl, pentenyl, hexenyl, and the like. Alkynyl groups include, for example, ethynyl, propynyl, butynyl, pentynyl, hexynyl, and the like. Carboxylic acid groups include, for example, formyl, acetyl, propionyl, butyryl, isobutyryl, valeryl, isovaleryl, and the like. Examples of the halogen atom include fluorine, chlorine, bromine, and iodine.
[0025] The electron transport material of the present disclosure is, in terms of solubility and interaction with a resin, a and R b are the same or different and each represents an alkyl group having 1 to 12 carbon atoms or an aryl group which may have a substituent, and the substituent is preferably a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, a hydroxyl group, a cyano group, an amino group, a nitro group or a halogenated alkyl group, and the substituent R b represents an aryl group which may have a substituent, and the substituent is preferably a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, a hydroxyl group, a cyano group, an amino group, a nitro group, or a halogenated alkyl group, and the substituent R a and R b are particularly preferred compounds in which both may have a substituent. For example, the following compounds 1-1 to 1-4 can be mentioned, and compound 1-1 is particularly preferred in terms of mobility and the wavelength of light absorbed.
[0026] [ka]
[0027] The content of the electron transport material is preferably 0.65 to 6.5% by mass based on the total solid content of the photosensitive layer. If the content of the electron transport material is less than 0.65% by mass, the light resistance and recovery from light damage may not be sufficient, whereas if the content of the electron transport material is more than 6.5% by mass, the electron transport material itself may become a trap, deteriorating the electrical properties of the photoreceptor. The content of the electron transport material is more preferably 1.0 to 5.2 mass %, and further preferably 1.4 to 3.5 mass %.
[0028] <Silica filler> The "silica" in silica filler means silicon dioxide (SiO2). Silica fillers that can be suitably used in the present disclosure are not limited by the manufacturing method, and examples thereof include dry process silica such as fumed silica obtained by burning silicon tetrachloride and arc process silica in which silica is microparticulated in the gas phase by high energy such as plasma; precipitation process silica synthesized under alkaline conditions using an aqueous sodium silicate solution as a raw material; wet process silica such as gel process silica synthesized under acidic conditions; and sol-gel process silica obtained by hydrolysis of an organic silane compound.
[0029] The silica filler may be surface-treated with a surface treatment agent such as hexamethyldisilazane, N-methyl-hexamethyldisilazane, N-ethyl-hexamethyldisilazane, hexamethyl-N-propyldisilazane, dimethyldichlorosilane, or polydimethylsiloxane to improve the electrical properties of the photoreceptor. Among these, dimethyldichlorosilane and hexamethyldisilazane are particularly preferred because they have good reactivity with the hydroxyl groups on the silica filler surface, making it possible to reduce the amount of hydroxyl groups on the silica filler surface, and as a result, it is possible to suppress the deterioration of the electrical properties of the photoreceptor due to moisture (humidity).
[0030] In the present disclosure, the silica filler treated with the above-mentioned surface treatment agent can be used, but commercially available silica fillers treated with a surface treatment agent can also be used. Examples of commercially available silica fillers include Nippon Aerosil Co., Ltd.'s product names: R972, R972V, R974, R976, RX200, NX130, NX90G, NX90S, NAX50, and RX50; Cabot Japan Co., Ltd.'s product names: TS610, TG709F, and TG6110G; and Admatech Co., Ltd.'s product name: YA010C.
[0031] The silica filler preferably has an average primary particle size in the range of 10 to 40 nm. If the average primary particle size of the silica filler is less than 10 nm, the silica filler has a strong agglomeration force, which makes it difficult to disintegrate, and the dispersibility of the silica filler may decrease.On the other hand, if the average primary particle size of the silica filler is more than 40 nm, the aggregate structure formed in the photosensitive layer becomes large, which makes it more likely to cause problems such as poor cleaning. The average primary particle size is more preferably 12 to 35 nm, and even more preferably 15 to 25 nm. The average primary particle diameter is the average value of particle diameters (major axis) in the Feret direction calculated by image analysis of 100 particles randomly observed as primary particles by observing the silica filler under a scanning electron microscope at a magnification of 30,000 to 300,000 times, for example 100,000 times.
[0032] The silica filler is preferably contained in an amount of 7 to 20% by mass based on the total solid content of the photosensitive layer. If the silica filler content is less than 7% by mass based on the total solid content of the photosensitive layer of the photoreceptor, the effect on abrasion resistance may not be sufficient, whereas if the silica filler content exceeds 20% by mass, the electrical properties of the photoreceptor may deteriorate. The content of the silica filler is more preferably 7 to 18 mass %, and particularly preferably 10 to 15 mass %.
[0033] The smaller the average primary particle size of the silica filler is and the greater the content of the silica filler is, the greater the contact area is and the worse the light resistance is, so the relationship between the content of the silica filler and the average primary particle size is important. The ratio w / d of the silica filler content w (mass %) to the average primary particle size d (nm) is preferably in the range of 0.20 to 0.95. If w / d is less than 0.20, the desired printing durability may not be obtained and cleaning failure may occur, whereas if w / d is more than 0.95, the content of the silica filler is too high relative to the average primary particle size, and light resistance may deteriorate. A more preferable range for w / d is 0.30 to 0.80, and a range of 0.45 to 0.75 is particularly preferable.
[0034] <Relationship between electron transport material and silica filler> The smaller the average primary particle size of the silica filler and the higher the content of the silica filler, the worse the light resistance becomes, so it is necessary to add a larger amount of electron transport material to obtain the desired light resistance. On the other hand, the larger the average primary particle size of the silica filler and the lower the content of the silica filler, the better the light resistance becomes, but the worse the potential stability becomes, so there is a limit to the amount of electron transport material that can be added. The ratio w / x of the content w (%) of the silica filler to the content x (%) of the electron transport substance is preferably in the range of 2.2 to 8.0. If w / x is less than 2.2, the content of the electron transport material is too high relative to the content of the silica filler, which may result in poor potential stability, whereas if w / x is more than 8.0, the content of the electron transport material is too low relative to the content of silica, which may result in failure to obtain the desired light resistance. A more preferable range for w / x is 2.8 to 7.0, and a particularly preferable range is 3.0 to 6.2.
[0035] The value d×x obtained by multiplying the average primary particle diameter d (nm) of the silica filler and the content x (mass %) of the electron transport substance is preferably in the range of 20-110. If d×x is less than 20, the content of the electron transport material is too small relative to the average primary particle size of the silica filler, so that the desired light resistance may not be obtained. On the other hand, if d×x is more than 110, the content of the electron transport material is too large relative to the average primary particle size of the silica filler, so that the potential stability may be deteriorated. A more preferable range of d×x is 20-90, and a range of 30-80 is particularly preferable.
[0036] (1) Electrophotographic Photoreceptor The photoreceptor of the present disclosure comprises at least a photosensitive layer on a conductive support. The photosensitive layer is preferably a laminated type photosensitive layer in which a charge generating layer containing a charge generating substance and a charge transport layer containing a charge transport substance (a hole transport substance and an electron transport substance) are laminated in this order, or a single-layered type photosensitive layer containing a charge generating substance and a charge transport substance (a hole transport substance and an electron transport substance), and is particularly preferably a laminated type photosensitive layer. In a single-layer photoreceptor having a single-layer photosensitive layer, the charge generating material is uniformly present in the photosensitive layer, so the electron travels a longer distance than in a laminated photoreceptor having a laminated photosensitive layer, and the laminated photoreceptor is more susceptible to the influence of a trapping material present in the photosensitive layer. When silica is contained in the photosensitive layer as in the photoreceptor of the present disclosure, the silica acts as a trap, so that a laminated photoreceptor is preferable from the viewpoint of electrical properties. The multi-layer photoreceptor of the present disclosure having a multi-layer photosensitive layer will be described below with reference to the drawings, but the present invention is not limited thereto.
[0037] FIG. 1 is a schematic cross-sectional view showing the configuration of a main part of a photoreceptor (multilayer type photoreceptor) F01 of the present disclosure. The laminated photoreceptor F01 has a photosensitive layer in which an undercoat layer F21, a charge generating layer F22 containing a charge generating material, and a charge transport layer F23 containing a hole transport material are laminated in this order on a conductive support F1. In the figure, Fa indicates the surface of the photoreceptor. The photoreceptor of the present disclosure may have a protective layer (surface protective layer) on the photosensitive layer.
[0038] <Conductive support F1> The conductive support (also referred to as "conductive substrate" or "substrate") functions as an electrode for the photoreceptor and as a support member, and the material constituting the conductive support is not particularly limited as long as it is a material used in the relevant technical field. Specific examples include metal materials such as aluminum, aluminum alloys, copper, zinc, stainless steel, and titanium, as well as polymer materials such as polyethylene terephthalate, nylon, and polystyrene, whose surfaces are laminated with metal foil, subjected to metal vapor deposition, or vapor-deposited or coated with a layer of a conductive compound such as a conductive polymer, tin oxide, or indium oxide, as well as hard paper and glass. Among these, aluminum is preferred from the viewpoint of ease of processing, and aluminum alloys such as JIS 3003, JIS 5000, and JIS 6000 are particularly preferred.
[0039] The shape of the conductive support is not limited to a cylindrical shape (drum shape) as shown in FIG. 2, but may be a sheet shape, a columnar shape, an endless belt shape, or the like. In addition, the surface of the conductive support may be subjected to anodizing film treatment, surface treatment with chemicals or hot water, coloring treatment, or diffuse reflection treatment such as surface roughening, as necessary, to prevent interference fringes caused by laser light, within a range that does not affect image quality.
[0040] <Undercoat layer F21> The photoreceptor of the present disclosure preferably includes an undercoat layer (also called an "intermediate layer") between the conductive support and the photosensitive layer. The undercoat layer generally covers the unevenness of the surface of the conductive support to make it uniform, improves the film-forming property of the laminated photosensitive layer, here the charge generating layer, suppresses peeling of the laminated photosensitive layer from the conductive support, and improves the adhesion between the conductive support and the laminated photosensitive layer. Specifically, it prevents the injection of charge from the conductive support into the laminated photosensitive layer, prevents a decrease in the chargeability of the laminated photosensitive layer, and prevents image fogging (so-called black spots), and maintains good electrophotographic properties such as chargeability throughout the life of the electrophotographic film.
[0041] The undercoat layer can be formed, for example, by dissolving a binder resin in a suitable solvent to prepare a coating liquid for the undercoat layer, coating this coating liquid on the surface of the conductive support, and removing the organic solvent by drying.
[0042] Examples of the binder resin include the same binder resin as that contained in the laminated photosensitive layer described later, as well as natural polymeric materials such as casein, gelatin, polyvinyl alcohol, and ethyl cellulose, and one or more of these can be used. The binder resin is required to have properties such as not dissolving or swelling in the solvent used when forming the photoreceptor layer on the undercoat layer, excellent adhesion to the conductive support, and flexibility. Therefore, among the above-mentioned binder resins, polyamide resins are preferred, and alcohol-soluble nylon resins are particularly preferred. Examples of alcohol-soluble nylon resins include homopolymer or copolymer nylons such as 6-nylon, 66-nylon, 610-nylon, 11-nylon, and 12-nylon, and resins obtained by chemically modifying nylons such as N-alkoxymethyl-modified nylons.
[0043] Examples of solvents for dissolving or dispersing resin materials include water, alcohols such as methanol, ethanol, and butanol, glymes such as methyl carbitol and butyl carbitol, chlorine-based solvents such as dichloroethane, chloroform, and trichloroethane, acetone, dioxolane, mixed solvents of two or more of these solvents, etc. Among these solvents, non-halogenated organic solvents are preferably used in consideration of the global environment.
[0044] The coating solution for the undercoat layer may contain inorganic compound fine particles. The inorganic compound fine particles of the undercoat layer have a different purpose from the inorganic compound fine particles of the outermost layer, and may be the same compound or different compounds. The inorganic compound fine particles can easily adjust the volume resistivity of the undercoat layer, can further suppress the injection of charges into the laminated type photosensitive layer, and can maintain the electrical characteristics of the photoreceptor under various environments. Examples of inorganic compound fine particles include fine particles of titanium oxide, aluminum oxide, aluminum hydroxide, and tin oxide. In the coating liquid for the undercoat layer, the ratio (C / D) of the total mass C of the binder resin and the inorganic compound particles to the mass D of the solvent is preferably from 1 / 99 to 40 / 60, particularly preferably from 2 / 98 to 30 / 70. The ratio E / F of the mass E of the binder resin to the mass F of the inorganic compound particles is preferably 90 / 10 to 1 / 99, and particularly preferably 70 / 30 to 5 / 95.
[0045] In order to disperse the inorganic compound particles in the coating liquid for the undercoat layer, known devices such as a ball mill, a sand mill, an attritor, a vibration mill, an ultrasonic disperser, and a paint shaker may be used. The method for applying the coating solution for the undercoat layer may be appropriately selected from among the most suitable methods taking into consideration the physical properties of the coating solution and productivity. Examples of the method include spraying, bar coating, roll coating, blade coating, ring coating, and dip coating. Among these, the dip coating method is a method in which a substrate is immersed in a coating tank filled with a coating liquid, and then pulled up at a constant speed or a gradually changing speed to form a layer on the surface of the substrate, and is relatively simple and has excellent productivity and cost, so that it can be suitably used for manufacturing photoreceptors. The apparatus used for the dip coating method may be provided with a coating liquid dispersion device, typically an ultrasonic generator, in order to stabilize the dispersibility of the coating liquid.
[0046] The solvent in the coating film may be removed by natural drying, but the solvent in the coating film may also be removed forcibly by heating. The temperature in such a drying step is not particularly limited as long as it is a temperature at which the solvent used can be removed, but a temperature of about 50 to 140°C is appropriate, and a temperature of about 80 to 130°C is particularly preferable. If the drying temperature is less than 50°C, the drying time may be long and the solvent may not evaporate sufficiently and remain in the photoreceptor layer, while if the drying temperature exceeds about 140°C, the electrical characteristics of the photoreceptor may deteriorate during repeated use, resulting in poor quality of the obtained image. Such temperature conditions are common not only to the formation of the undercoat layer but also to the formation of layers such as a laminated type photosensitive layer, which will be described later, and other treatments. When the conductive support is made of aluminum, a layer containing alumite (alumite layer) may be formed as the undercoat layer.
[0047] The thickness of the undercoat layer is not particularly limited, but is preferably 0.01 to 20 μm, and more preferably 0.05 to 10 μm. If the thickness of the undercoat layer is less than 0.01 μm, it will not function as an undercoat layer, and it will not be possible to cover defects in the conductive support to obtain a uniform surface, and it may not be possible to prevent injection of charges from the conductive support into the laminated photosensitive layer. On the other hand, if the thickness of the undercoat layer is more than 20 μm, it will be difficult to form a uniform undercoat layer, and the sensitivity of the photoreceptor may also decrease.
[0048] <Charge generation layer F22> The charge generating layer has a function of generating charges by absorbing light irradiated by, for example, semiconductor laser light in an image forming apparatus, and contains a charge generating substance as a main component and, if necessary, a binder resin and additives.
[0049] The charge generating material can be a compound used in the field, specifically, azo pigments such as monoazo pigments, bisazo pigments and trisazo pigments; indigo pigments such as indigo and thioindigo; perylene pigments such as peryleneimide and perylene acid anhydride; polycyclic quinone pigments such as anthraquinone and pyrenequinone; phthalocyanine pigments such as metal phthalocyanine and metal-free phthalocyanine such as titanyl phthalocyanine; organic photoconductive materials such as squarylium dyes, pyrylium salts, thiopyrylium salts, triphenylmethane dyes; and inorganic photoconductive materials such as selenium and amorphous silicon, and can be appropriately selected and used from those having sensitivity in the exposure wavelength range. These charge generating materials can be used alone or in combination of two or more. Among these charge generating materials, those represented by the following general formula (A):
[0050] [ka]
[0051] (In the formula, X 1 , X 2 , X 3 and X 4 are the same or different and each is a halogen atom, an alkyl group, or an alkoxy group, and r, s, y, and z are the same or different and each is an integer of 0 to 4. It is preferable to use titanyl phthalocyanine represented by the following formula: Titanyl phthalocyanine is a charge-generating material that has high charge generation efficiency and charge injection efficiency in the emission wavelength range (near-infrared light) of currently commonly used laser light and LED light. It generates a large amount of charge by absorbing light and can efficiently inject the generated charge into the hole-transporting material without accumulating it internally.
[0052] The titanyl phthalocyanine represented by the general formula (A) can be produced by known production methods such as the method described in Phthalocyanine Compounds by Moser, Frank H. and Arthur L. Thomas, Reinhold Publishing Corp., New York, 1963. For example, among the titanyl phthalocyanine compounds represented by the general formula (A), in the case of an unsubstituted titanyl phthalocyanine in which r, s, y, and z are 0, it can be obtained by synthesizing dichlorotitanyl phthalocyanine by heating and melting phthalonitrile and titanium tetrachloride or by heating and reacting them in a suitable solvent such as α-chloronaphthalene, and then hydrolyzing the resultant with a base or water. Alternatively, the titanyl phthalocyanine composition can be produced by reacting isoindoline with a titanium tetraalkoxide such as tetrabutoxytitanium under heating in a suitable solvent such as N-methylpyrrolidone.
[0053] The method for forming the charge generation layer includes a method of vacuum-depositing the charge generation material on the conductive support, and a method of dispersing the charge generation material in a solvent and applying a coating liquid for the charge generation layer onto the conductive support. Among these, a method of dispersing the charge generation material in a binder resin solution obtained by mixing a binder resin in a solvent by a conventionally known method and applying the coating liquid for the charge generation layer onto the conductive support is preferred. This method will be described below.
[0054] The binder resin is not particularly limited, and any resin known in the art can be used. Examples of the binder resin include polyester, polystyrene, polyurethane, phenolic resin, alkyd resin, melamine resin, epoxy resin, silicone resin, acrylic resin, methacrylic resin, polycarbonate, polyarylate, polyphenoxy, polyvinyl butyral, and polyvinyl formal resins, as well as copolymer resins containing two or more of the repeating units constituting these resins. Examples of the copolymer resin include insulating resins such as vinyl chloride-vinyl acetate copolymer resin, vinyl chloride-vinyl acetate-maleic anhydride copolymer resin, and acrylonitrile-styrene copolymer resin. These resins can be used alone or in combination of two or more.
[0055] Examples of the solvent include halogenated hydrocarbons such as dichloromethane and dichloroethane, ketones such as acetone, methyl ethyl ketone and cyclohexanone, esters such as ethyl acetate and butyl acetate, ethers such as tetrahydrofuran (THF) and dioxane, alkyl ethers of ethylene glycol such as 1,2-dimethoxyethane, aromatic hydrocarbons such as benzene, toluene and xylene, and aprotic polar solvents such as N,N-dimethylformamide and N,N-dimethylacetamide. These solvents can be used alone or in combination of two or more.
[0056] The compounding ratio between the charge generating substance and the binder resin is preferably such that the proportion of the charge generating substance is within a range of 10 to 99 mass %. If the ratio of the charge generating material is less than 10% by mass, the sensitivity may decrease. On the other hand, if the ratio of the charge generating material is more than 99% by mass, not only the film strength of the charge generating layer decreases, but also the dispersibility of the charge generating material decreases, the number of coarse particles increases, and the surface charge decreases in areas other than those that should be erased by exposure, resulting in image defects, particularly image fogging called black spots, in which toner adheres to a white background and tiny black spots are formed.
[0057] Before dispersing the charge generating material in the binder resin solution, the charge generating material may be pulverized in advance using a pulverizer such as a ball mill, a sand mill, an attritor, a vibration mill, or an ultrasonic disperser. Examples of dispersing machines used when dispersing the charge generating material in the binder resin solution include a paint shaker, a ball mill, a sand mill, etc. Appropriate dispersion conditions may be selected so as to prevent the incorporation of impurities due to wear of the container and members constituting the dispersing machine. The coating liquid for the charge generating layer may be applied by the same method as the coating liquid for the undercoat layer, and a dip coating method is particularly preferred.
[0058] The thickness of the charge generating layer is not particularly limited, but is preferably 0.05 to 5 μm, and more preferably 0.1 to 1 μm. If the thickness of the charge generating layer is less than 0.05 μm, the efficiency of light absorption decreases, and the sensitivity of the photoconductor may decrease. On the other hand, if the thickness of the charge generating layer exceeds 5 μm, the charge transfer inside the charge generating layer becomes the rate-limiting step in the process of erasing the charge on the surface of the laminated photosensitive layer, and the sensitivity of the photoconductor may decrease.
[0059] <Charge transport layer F23> The charge transport layer has the function of receiving the charges generated by the charge generating substance and transporting them to the surface of the photoreceptor, and contains a hole transport substance, a binder resin, an electron transport substance, a silica filler, and additives as required.
[0060] As the hole transport material, compounds used in the art can be used. Specific examples thereof include carbazole derivatives, pyrene derivatives, oxazole derivatives, oxadiazole derivatives, thiazole derivatives, thiadiazole derivatives, triazole derivatives, imidazole derivatives, imidazolone derivatives, imidazolidine derivatives, bisimidazolidine derivatives, styryl compounds, hydrazone compounds, polycyclic aromatic compounds, indole derivatives, pyrazoline derivatives, oxazolone derivatives, benzimidazole derivatives, quinazoline derivatives, benzofuran derivatives, acridine derivatives, phenazine derivatives, aminostilbene derivatives, triarylamine derivatives, triarylmethane derivatives, phenylenediamine derivatives, stilbene derivatives, butadiene derivatives, enamine derivatives, benzidine derivatives, polymers having groups derived from these compounds in the main chain or side chain (poly-N-vinylcarbazole, poly-1-vinylpyrene, ethylcarbazole-formaldehyde resin, triphenylmethane polymer, poly-9-vinylanthracene, etc.), and polysilanes. These hole transport materials can be used alone or in combination of two or more.
[0061] Among these various hole transporting substances, stilbene derivatives, butadiene derivatives, enamine derivatives, and compounds in which a plurality of these compounds are combined are preferred in terms of electrical properties, durability, and chemical stability. Stilbene derivatives are more preferred because they have light absorption in the wavelength range of 300 to 480 nm and have a wide range of absorption as hole transporting substances. These derivatives are represented by the following general formula (II):
[0062] [ka]
[0063] (In the formula, R 1 , R 2 , R 5 and R 6 are the same or different and each is an alkyl group, an alkoxy group, an aryl group, or an aralkyl group; m, n, p, and q are the same or different and each is an integer of 0 to 3; R 3 and R 4are the same or different and are a hydrogen atom or an alkyl group. The stilbene compounds represented by the following formula are particularly preferred in that they cause little increase in residual potential and little deterioration in sensitivity and can exhibit good electrophotographic properties.
[0064] The substituent R in the general formula (II) 1 , R 2 , R 5 and R 6 This article explains: Examples of the alkyl group include alkyl groups having 1 to 6 carbon atoms, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, and n-hexyl. Examples of the alkoxy group include alkoxy groups having 1 to 6 carbon atoms, such as methoxy, ethoxy, n-propoxy, isopropoxy, tert-butoxy, n-pentyloxy, and n-hexyloxy. Examples of the aryl group include phenyl, naphthyl, anthryl, phenanthryl, fluorenyl, biphenylyl, and o-terphenyl. Aralkyl groups include, for example, benzyl, phenethyl, benzhydryl, trityl, and the like. Examples of the halogen atom include fluorine, chlorine, bromine, and iodine.
[0065] Substituent R 1 , R 2 , R 5 and R 6 The indices m, n, p and q are the same or different and are integers of 0 to 3, and when the index is 2 or more, each substituent may be different from each other. In addition, the substituent R in the general formula (II) 3 and R 4 Examples of the alkyl group include alkyl groups having 1 to 3 carbon atoms, such as methyl, ethyl, n-propyl, and isopropyl. The stilbene compound represented by the general formula (II) can be synthesized, for example, by the method described in Japanese Patent No. 3272257.
[0066] Examples of the stilbene compound represented by the general formula (II) include the following compounds 2-1 to 2-3, and compound 2-1 is particularly preferred in terms of printing durability when used in a laminated photosensitive layer.
[0067] [ka]
[0068] A preferred method for forming the charge transport layer is to disperse a hole transport material in a binder resin solution obtained by mixing a binder resin in a solvent by a conventionally known method, and then coat the charge transport layer coating liquid on the charge generating layer. This method is described below.
[0069] The binder resin is not particularly limited, and any resin having binding properties that is used in the art can be used, and it is preferable that the binder resin has excellent compatibility with the hole transport material. Specific examples include vinyl polymer resins such as polymethyl methacrylate, polystyrene, and polyvinyl chloride, and copolymer resins thereof, as well as resins such as polycarbonate, polyester, polyester carbonate, polysulfone, phenoxy resin, epoxy resin, silicone resin, polyarylate, polyamide, polyether, polyurethane, polyacrylamide, phenol resin, and polyphenylene oxide, and thermosetting resins obtained by partially crosslinking these resins. These binder resins can be used alone or in combination of two or more. Among these, polystyrene, polycarbonate, polyarylate and polyphenylene oxide have a volume resistivity of 10 13 These are preferred because they have a hardness of Ω or more, are excellent in electrical insulation, and are also excellent in film-forming properties and potential characteristics. Polycarbonate and polyarylate are more preferred, and polycarbonate is particularly preferred.
[0070] The charge transport layer may contain additives such as antioxidants, plasticizers, leveling agents, and the like. The antioxidant includes tribenzylamine. Examples of the plasticizer include dibasic acid esters such as phthalic acid esters, fatty acid esters, phosphate esters, chlorinated paraffin, and epoxy type plasticizers. The leveling agent may be, for example, a silicon-based leveling agent.
[0071] Examples of the solvent include aromatic hydrocarbons such as benzene, toluene, xylene, and monochlorobenzene; halogenated hydrocarbons such as dichloromethane and dichloroethane; ethers such as tetrahydrofuran, dioxane, and dimethoxymethyl ether; and aprotic polar solvents such as N,N-dimethylformamide. If necessary, a solvent such as alcohols, acetonitrile, or methyl ethyl ketone can also be added. These solvents can be used alone or in combination of two or more. Among these solvents, for example, non-halogenated organic solvents can be preferably used in consideration of the global environment. The ratio (G / H) of the mass G of the hole transport substance to the mass H of the binder resin is preferably, for example, about 10 / 12 to 10 / 30.
[0072] The thickness of the charge transport layer is not particularly limited, but is preferably about 20 to 40 μm, and more preferably about 25 to 40 μm. If the thickness of the charge transport layer is less than 20 μm, the effect on light resistance may not be sufficient, whereas if the thickness of the charge transport layer is more than 40 μm, the electrical properties may deteriorate.
[0073] (2) Process cartridge The process cartridge of the present disclosure is characterized by comprising the photosensitive member of the present disclosure, and at least one selected from a charging means for charging the photosensitive member, a developing means for developing an electrostatic latent image formed by exposure to light to form a toner image, and a cleaning means for removing toner remaining on the photosensitive member. For example, the process cartridge of the present disclosure is configured by integrating the photoconductor, charging device, developing device, and cleaning device of the present disclosure with a support member. When such a process cartridge is incorporated into the image forming apparatus 100, each of the components of the process cartridge is provided in the image forming apparatus 100. The process cartridge is detachable from the image forming apparatus 100, which makes it easy to replace it when it becomes worn out.
[0074] (3) Image forming device The image forming apparatus of the present disclosure is characterized by comprising at least the photoconductor of the present disclosure, a charging means for charging the photoconductor, an exposure means for exposing the charged photoconductor to light to form an electrostatic latent image, a developing means for developing the electrostatic latent image to form a toner image (make it visible), and a transfer means for transferring the toner image onto a recording medium. The image forming apparatus of the present disclosure may include a fixing means for fixing the transferred toner image onto a recording medium to form an image, a cleaning means for removing and recovering toner remaining on the photosensitive member, and a discharging means for discharging surface charges remaining on the photosensitive member. The image forming apparatus of the present disclosure and its operation will be described below with reference to the drawings, but the image forming apparatus of the present disclosure is not limited thereto.
[0075] FIG. 2 is a schematic side view showing the configuration of a main part of the image forming apparatus of the present disclosure. 2 includes the photoreceptor 1 of the present disclosure, an exposure means (semiconductor laser) 31, a charging means (charger) 32, a developing means (developer) 33, a transfer means (transfer charger) 34, a conveyor belt (not shown), a fixing means (fixer) 35, and a cleaning means (cleaner) 36. Reference numeral 51 denotes a recording medium (recording paper or transfer paper).
[0076] Photoconductor 1 is rotatably supported by the main body of image forming apparatus 100, and is driven to rotate around rotation axis 44 in the direction of arrow 41 by driving means (not shown). The driving means includes, for example, an electric motor and a reduction gear, and transmits its driving force to a conductive support constituting the core body of photoconductor 1, thereby driving and rotating photoconductor 1 at a predetermined peripheral speed. Charging means (charger) 32, exposure means 31, developing means (developer) 33, transfer means (transfer charger) 34, and cleaning means (cleaner) 36 are provided in this order along the outer circumferential surface of photoconductor 1 from the upstream side to the downstream side in the rotation direction of photoconductor 1 indicated by arrow 41.
[0077] The charger 32 is a charging means for uniformly charging the outer circumferential surface of the photoreceptor 1 to a predetermined potential. The exposure means 31 has a semiconductor laser as a light source, and irradiates the surface of the photoreceptor 1 between the charger 32 and the developer 33 with a laser beam light output from the light source, thereby exposing the charged outer peripheral surface of the photoreceptor 1 according to image information. The light is repeatedly scanned in the direction of extension of the rotation axis 44 of the photoreceptor 1, which is the main scanning direction, and these are focused to sequentially form electrostatic latent images on the surface of the photoreceptor 1. In other words, the charge amount of the photoreceptor 1, which has been uniformly charged by the charger 32, differs depending on whether it is irradiated with the laser beam or not, and an electrostatic latent image is formed.
[0078] The developing device 33 is a developing means that develops the electrostatic latent image formed on the surface of the photoconductor 1 by exposure with a developer (toner), and is provided facing the photoconductor 1. The developing device 33 includes a developing roller 33a that supplies toner to the outer peripheral surface of the photoconductor 1, and a casing 33b that rotatably supports the developing roller 33a about a rotation axis parallel to the rotation axis 44 of the photoconductor 1 and contains a developer including toner in its internal space.
[0079] The transfer charger 34 is a transfer means that transfers a toner image, which is a visible image formed on the outer peripheral surface of the photoconductor 1 by development, onto a transfer paper 51, which is a recording medium, supplied between the photoconductor 1 and the transfer charger 34 from the direction of the arrow 42 by a transport means (not shown). The transfer charger 34 is, for example, a contact type transfer means that includes a charging means and transfers the toner image onto the transfer paper 51 by applying a charge of the opposite polarity to that of the toner to the transfer paper 51.
[0080] The cleaner 36 is a cleaning means for removing and recovering the toner remaining on the outer peripheral surface of the photoreceptor 1 after the transfer operation by the transfer charger 34, and includes a cleaning blade 36a for removing the toner remaining on the outer peripheral surface of the photoreceptor 1, and a recovery casing 36b for containing the toner removed by the cleaning blade 36a. The cleaner 36 is also provided together with a static elimination lamp (not shown).
[0081] Furthermore, in the image forming apparatus 100, a fixing device 35, which is a fixing means for fixing a transferred image, is provided downstream of the conveyance of the transfer paper 51 that has passed between the photoconductor 1 and the transfer charger 34. The fixing device 35 includes a heating roller 35a having a heating means (not shown), and a pressure roller 35b that is provided opposite the heating roller 35a and is pressed against the heating roller 35a to form a contact portion. Reference numeral 37 denotes a separating means for separating the transfer paper from the photosensitive member, and reference numeral 38 denotes a casing for accommodating each of the means of the image forming apparatus.
[0082] The image forming operation by this image forming apparatus 100 is carried out as follows. First, when the photoconductor 1 is rotated in the direction of arrow 41 by the driving means, the surface of the photoconductor 1 is uniformly charged to a predetermined positive potential by the charger 32, which is provided upstream of the image-forming point of the light by the exposure means 31 in the rotational direction of the photoconductor 1.
[0083] Next, light according to image information is irradiated from exposure means 31 onto the surface of photoreceptor 1. This exposure removes surface charge from the areas of photoreceptor 1 irradiated with light, creating a difference in surface potential between the areas irradiated with light and the areas not irradiated with light, forming an electrostatic latent image. Toner is supplied from a developing device 33, which is provided downstream in the rotational direction of the photoconductor 1 from the imaging point of the light by the exposure means 31, to the surface of the photoconductor 1 on which the electrostatic latent image is formed, thereby developing the electrostatic latent image and forming a toner image.
[0084] In synchronization with the exposure of the photoconductor 1, a transfer paper 51 is supplied between the photoconductor 1 and the transfer charger 34. The transfer charger 34 gives the supplied transfer paper 51 a charge of the opposite polarity to that of the toner, and the toner image formed on the surface of the photoconductor 1 is transferred onto the transfer paper 51. The transfer paper 51 onto which the toner image has been transferred is transported by the transport means to the fixing device 35, and is heated and pressurized as it passes through the contact area between the heating roller 35a and the pressure roller 35b of the fixing device 35, and the toner image is fixed onto the transfer paper 51 to form a robust image. The transfer paper 51 on which the image has been formed in this way is discharged to the outside of the image forming apparatus 100 by the transport means.
[0085] Meanwhile, the toner remaining on the surface of the photoreceptor 1 after the transfer of the toner image by the transfer charger 34 is peeled off from the surface of the photoreceptor 1 and collected by the cleaner 36. The charge on the surface of the photoreceptor 1 from which the toner has been removed in this manner is removed by light from a discharging lamp, and the electrostatic latent image on the surface of the photoreceptor 1 disappears. The photoreceptor 1 is then rotated again, and the series of operations starting with charging are repeated again to form images continuously.
[0086] The image forming apparatus 100 is a monochrome image forming apparatus (printer), but may be, for example, a color image forming apparatus of an intermediate transfer type capable of forming a color image. Specifically, it may be a so-called tandem type full-color image forming apparatus in which a plurality of electrophotographic photosensitive members on which toner images are respectively formed are arranged in a predetermined direction (for example, the horizontal direction H or the approximately horizontal direction H). The image forming apparatus 100 may also be another color image forming apparatus, a copying machine, a multifunction machine, or a facsimile machine. EXAMPLES
[0087] The present disclosure will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to these examples as long as the gist of the disclosure is not exceeded. In the examples and comparative examples, a multi-layer type photoreceptor having a multi-layer type photosensitive layer was used, but the same effect can be obtained by using a single-layer type photoreceptor having a single-layer type photosensitive layer. In the examples and comparative examples, the physical properties of the materials used were measured by the following methods.
[0088] (1) Maximum absorption wavelength λ of the electron transport material max The spectral absorption spectrum of the electron transport material is measured in the wavelength region of 400 to 900 nm using an ultraviolet-visible spectrophotometer (Shimadzu Corporation, UV-VIS SPECTROPHOTOMETER, model: UV-2450). If the maximum value is in the wavelength region of 500 to 600 nm, the wavelength is defined as the maximum absorption wavelength λ max Let us assume that.
[0089] (2) Average primary particle size of silica filler Using a scanning electron microscope (SEM, manufactured by Hitachi High-Technologies Corporation, model: S-4800), photograph the silica particles at a magnification of 30,000 to 300,000 times, for example, 100,000 times, and from the obtained image, 100 silica particles are arbitrarily observed as primary particles. The average particle size (major axis) in the Feret direction is calculated by image analysis, and this is defined as the average primary particle size (nm).
[0090] [Example 1] (Formation of Undercoat Layer) Three parts by weight of titanium oxide (manufactured by Ishihara Sangyo Kaisha, Ltd., product name: Tiebaque TTO-D-1) and two parts by weight of copolymer polyamide (nylon) (manufactured by Toray Industries, Inc., product name: Amilan (registered trademark), grade: CM8000) were added to 25 parts by weight of methyl alcohol, and the mixture was dispersed for eight hours using a paint shaker to prepare 3 liters of coating solution for the undercoat layer. The obtained coating liquid for the undercoat layer was filled into a coating tank, and an aluminum drum-shaped support having a diameter of 30 mm and a length of 255 mm as the conductive support F1 was immersed in it and then removed. The obtained coating film was allowed to dry naturally, thereby forming an undercoat layer F21 with a thickness of 1 μm on the conductive support F1.
[0091] (Formation of Charge Generation Layer) Titanyl phthalocyanine represented by the following structural formula, which was to be used as a charge generating material, was prepared in advance. [ka]
[0092] 29.2 g of diiminoisoindoline and 200 ml of sulfolane were mixed, and 17.0 g of titanium tetraisopropoxide was added and reacted under a nitrogen atmosphere at 140° C. for 2 hours. The resulting reaction mixture was allowed to cool, and the precipitate was collected by filtration, washed successively with chloroform and a 2% aqueous hydrochloric acid solution, further washed successively with water and methanol, and dried to obtain 25.5 g of blue-purple crystals. As a result of chemical analysis of the obtained compound, it was confirmed that it was titanyl phthalocyanine represented by the above structural formula (yield 88.5%). 1 part by weight of the obtained titanyl phthalocyanine and 1 part by weight of butyral resin (manufactured by Sekisui Chemical Co., Ltd., product name: S-LEC BM-2) were added to 98 parts by weight of methyl ethyl ketone, and the mixture was dispersed for 2 hours using a paint shaker to prepare 3 liters of a coating solution for the charge generating layer. The obtained coating liquid for the charge generating layer was applied onto the undercoat layer F21 by the same immersion method as in the case of forming the undercoat layer, and the obtained coating film was allowed to dry naturally to form a charge generating layer F22 with a thickness of 0.3 μm.
[0093] (Formation of charge transport layer) Next, 3.4 g of silica filler (average primary particle size 16 nm, dimethylchlorosilane surface treatment, Nippon Aerosil Co., Ltd., product name: AEROSIL (registered trademark) R972) was added to 30.3 g of tetrahydrofuran and suspended, followed by stirring for 30 hours. The obtained silica filler suspension was added with 10.0 g of compound 2-1 (stilbene derivative) represented by the following structural formula as a hole transport material, 0.30 g of tribenzylamine (Tokyo Chemical Industry Co., Ltd.) as an antioxidant, 19.0 g of polycarbonate (Teijin Chemical Co., Ltd., product name: TS2050), and compound 1-1 (λ 2 ) represented by the following structural formula (wherein Ph represents a phenyl group) as an electron transport material. max = 528 nm) and 104.4 g of tetrahydrofuran were added and mixed.
[0094] [ka]
[0095] [ka]
[0096] The mixture was stirred for 5 minutes using an ultra-atomizer (manufactured by Yoshida Kikai Kogyo Co., Ltd., product name: Damatri System), and then dispersed 10 times using a particle dispersion device (manufactured by Microfluidics Co., Ltd., model: Microfluidizer M-110P) to prepare 168.3 g of the coating solution for the charge transport layer. The obtained coating liquid for the charge transport layer was applied onto the charge generation layer F22 by the same immersion method as in the case of forming the undercoat layer, and the obtained coating film was dried at a temperature of 115° C. for 1.5 hours to form a charge transport layer F23 with a thickness of 35 μm, thereby producing the photoreceptor F01 of Example 1 shown in FIG. 1.
[0097] The above compound 1-1 was prepared in advance based on the method described in Japanese Patent No. 4,041,741, and the above compound 2-1 (stilbene derivative) was prepared in advance based on the method described in Japanese Patent No. 3,272,257.
[0098] Example 2 In preparing the coating solution for the charge transport layer, the electron transport material was replaced with Compound 1-2 (λ max A photoreceptor of Example 2 was prepared in the same manner as in Example 1, except that a 100 nm wavelength region (λ / 200 nm) was used. The above compound 1-2 was prepared in advance based on the method described in Japanese Patent No. 4041741. [ka]
[0099] Example 3 In preparing the coating solution for the charge transport layer, the electron transport material was replaced with Compound 1-3 (λ max A photoreceptor of Example 3 was prepared in the same manner as in Example 1, except that a 100 nm wavelength region (.lambda.=580 nm) was used. The above compound 1-3 was prepared in advance based on the method described in Japanese Patent No. 4041741. [ka]
[0100] Example 4 The photoconductor of Example 4 was prepared in the same manner as in Example 1, except that in preparing the coating solution for the charge transport layer, the amount of silica filler (average primary particle diameter 40 nm, surface treatment with hexamethyldisilazane, manufactured by Nippon Aerosil Co., Ltd., product name: AEROSIL (registered trademark) RX-50) was changed to 2.24 g, the amount of tetrahydrofuran was changed to 29.8 g, the amount of electron transport material added to the suspension was changed to 0.45 g, and the amount of tetrahydrofuran was changed to 98.2 g.
[0101] Example 5 The photoreceptor of Example 5 was prepared in the same manner as in Example 1, except that in the preparation of the coating liquid for the charge transport layer, the amount of silica filler was changed to 6.21 g and the amount of tetrahydrofuran added to the suspension was changed to 115.7 g.
[0102] Example 6 The photoconductor of Example 6 was prepared in the same manner as in Example 1, except that in preparing the coating solution for the charge transport layer, the amount of silica filler (average primary particle diameter 12 nm, surface treatment with dimethylchlorosilane, manufactured by Nippon Aerosil Co., Ltd., product name: AEROSIL (registered trademark) R974) was changed to 2.64 g, the amount of tetrahydrofuran was changed to 30.4 g, the amount of electron transport material added to the suspension was changed to 1.10 g, and the amount of tetrahydrofuran was changed to 101.8 g.
[0103] Example 7 The photoreceptor of Example 7 was prepared in the same manner as in Example 1, except that in the preparation of the coating solution for the charge transport layer, the amount of silica filler was changed to 3.68 g, the amount of tetrahydrofuran was changed to 29.8 g, the amount of electron transport material added to the suspension was changed to 0.50 g, and the amount of tetrahydrofuran was changed to 104.13 g.
[0104] Example 8 The photoconductor of Example 8 was prepared in the same manner as in Example 1, except that in preparing the coating solution for the charge transport layer, the amount of silica filler (average primary particle diameter 12 nm, surface treatment with dimethylchlorosilane, manufactured by Nippon Aerosil Co., Ltd., product name: AEROSIL (registered trademark) R974) was changed to 2.59 g, the amount of tetrahydrofuran was changed to 29.8 g, the amount of electron transport material added to the suspension was changed to 0.50 g, and the amount of tetrahydrofuran was changed to 99.77 g.
[0105] Example 9 The photoconductor of Example 9 was prepared in the same manner as in Example 1, except that in the preparation of the coating liquid for the charge transport layer, the amount of silica filler (average primary particle diameter 30 nm, surface treatment with hexamethyldisilazane, manufactured by Nippon Aerosil Co., Ltd., product name: AEROSIL (registered trademark) NAX-50) was changed to 6.29 g, the amount of tetrahydrofuran was changed to 30.7 g, the amount of electron transport material added to the suspension was changed to 1.40 g, and the amount of tetrahydrofuran was changed to 117.3 g.
[0106] Example 10 The photoreceptor of Example 10 was prepared in the same manner as in Example 1, except that in the preparation of the coating solution for the charge transport layer, the amount of silica filler was changed to 1.58 g, the amount of tetrahydrofuran was changed to 30.0 g, the amount of electron transport material added to the suspension was changed to 0.70 g, and the amount of tetrahydrofuran was changed to 96.3 g.
[0107] Example 11 The photoconductor of Example 11 was prepared in the same manner as in Example 1, except that in the preparation of the coating liquid for the charge transport layer, the amount of silica filler (average primary particle diameter 30 nm, surface treatment with hexamethyldisilazane, manufactured by Nippon Aerosil Co., Ltd., product name: AEROSIL (registered trademark) NAX-50) was changed to 10.1 g, and the amount of tetrahydrofuran added to the suspension was changed to 131.3 g.
[0108] Example 12 The photoconductor of Example 12 was prepared in the same manner as in Example 1, except that in preparing the coating solution for the charge transport layer, the amount of silica filler (average primary particle diameter 30 nm, surface treatment with hexamethyldisilazane, manufactured by Nippon Aerosil Co., Ltd., product name: AEROSIL (registered trademark) NAX-50) was changed to 2.21 g, the amount of tetrahydrofuran was changed to 29.5 g, the amount of electron transport material added to the suspension was changed to 0.18 g, and the amount of tetrahydrofuran was changed to 97.3 g.
[0109] Example 13 The photoconductor of Example 13 was prepared in the same manner as in Example 1, except that in preparing the coating solution for the charge transport layer, the amount of silica filler (average primary particle diameter 12 nm, surface treatment with dimethylchlorosilane, manufactured by Nippon Aerosil Co., Ltd., product name: AEROSIL (registered trademark) R974) was changed to 8.00 g, the amount of tetrahydrofuran was changed to 32.0 g, the amount of electron transport material added to the suspension was changed to 2.70 g, and the amount of tetrahydrofuran was changed to 128.00 g.
[0110] Example 14 The photoconductor of Example 14 was prepared in the same manner as in Example 1, except that in preparing the coating solution for the charge transport layer, the amount of silica filler (number average primary particle diameter 7 nm, surface treatment with dimethylchlorosilane, manufactured by Nippon Aerosil Co., Ltd., product name: AEROSIL (registered trademark) R976) was changed to 3.39 g, the amount of tetrahydrofuran was changed to 30.5 g, the amount of electron transport material added to the suspension was changed to 1.20 g, and the amount of tetrahydrofuran was changed to 105.06 g.
[0111] Example 15 The photoconductor of Example 15 was prepared in the same manner as in Example 1, except that in the preparation of the coating liquid for the charge transport layer, the amount of silica filler (average primary particle diameter 100 nm, surface treatment with hexamethyldisilazane, manufactured by Nippon Aerosil Co., Ltd., product name: AEROSIL (registered trademark) VPRX-40) was changed to 7.45 g, the amount of tetrahydrofuran was changed to 29.8 g, the amount of electron transport material added to the suspension was changed to 0.50 g, and the amount of tetrahydrofuran was changed to 119.20 g.
[0112] Example 16 In preparing the coating solution for the charge transport layer, the electron transport material was replaced with Compound 1-4 (λ max A photoreceptor of Example 16 was prepared in the same manner as in Example 1, except that a 100 nm wavelength region (.lambda.=553 nm) was used. The above compound 1-4 was prepared in advance based on the method described in Japanese Patent No. 4041741. In the formula, Ph represents a phenyl group, and t-Bu represents a tert-butyl group. [ka]
[0113] (Example 17) The photoreceptor of Example 17 was prepared in the same manner as in Example 1, except that in the preparation of the coating liquid for the charge transport layer, a silica filler (average primary particle diameter 16 nm, hexamethyldisilazane surface treatment, manufactured by Nippon Aerosil Co., Ltd., product name: AEROSIL (registered trademark) NX130) was used.
[0114] (Example 18) The photoreceptor of Example 18 was prepared in the same manner as in Example 1, except that in the preparation of the coating solution for the charge transport layer, the amount of silica filler was changed to 3.86 g, the amount of tetrahydrofuran was changed to 31.2 g, the amount of electron transport material added to the suspension was changed to 1.92 g, and the amount of tetrahydrofuran was changed to 109.10 g.
[0115] (Example 19) In the preparation of the charge transport layer coating solution, the amount of silica filler (average primary particle size 12 nm, surface treatment with dimethylchlorosilane, manufactured by Nippon Aerosil Co., Ltd., product name: AEROSIL (registered trademark) R974) was changed to 3.11 g, the amount of tetrahydrofuran was changed to 29.8 g, the amount of electron transport material added to the suspension was changed to 0.53 g, and the amount of tetrahydrofuran was changed to 102.75 g. The photoconductor of Example 19 was prepared in the same manner as in Example 1.
[0116] Comparative Example 1 The photoconductor of Comparative Example 1 was prepared in the same manner as in Example 1, except that in the preparation of the coating solution for the charge transport layer, the amount of silica filler was changed to 2.87 g, the amount of tetrahydrofuran was changed to 30.9 g, the amount of electron transport material added to the suspension was changed to 1.60 g, and the amount of tetrahydrofuran was changed to 104.18 g.
[0117] Comparative Example 2 The photoconductor of Comparative Example 2 was prepared in the same manner as in Example 1, except that in preparing the coating solution for the charge transport layer, the amount of silica filler (average primary particle diameter 12 nm, surface treatment with dimethylchlorosilane, manufactured by Nippon Aerosil Co., Ltd., product name: AEROSIL (registered trademark) R974) was changed to 7.62 g, the amount of tetrahydrofuran was changed to 30.5 g, the amount of electron transport material added to the suspension was changed to 1.17 g, and the amount of tetrahydrofuran was changed to 121.88 g.
[0118] Comparative Example 3 The photoconductor of Comparative Example 3 was prepared in the same manner as in Example 1, except that in the preparation of the coating solution for the charge transport layer, no silica filler was used, and instead 10.0 g of compound 2-1 as a hole transport material, 0.30 g of tribenzylamine (manufactured by Tokyo Chemical Industry Co., Ltd., product name: tribenzylamine) as an antioxidant, 19.0 g of polycarbonate (manufactured by Teijin Chemical Co., Ltd., product name: TS2050) and 1.0 g of compound 1-1 as an electron transport material were added to 107.4 g of tetrahydrofuran as a solvent, mixed, and stirred for 30 hours.
[0119] Comparative Example 4 The photoconductor of Comparative Example 4 was prepared in the same manner as in Example 1, except that in the preparation of the coating solution for the charge transport layer, the amount of silica filler was changed to 3.26 g, the amount of tetrahydrofuran was changed to 29.3 g, no electron transport material was added to the suspension, and the amount of tetrahydrofuran was changed to 100.92 g.
[0120] Comparative Example 5 In preparing the coating solution for the charge transport layer, the dye CISolvent Red 52 (λ max A photoreceptor of Comparative Example 5 was prepared in the same manner as in Example 1, except that a photoreceptor having a wavelength of 500 nm (=540 nm, manufactured by Kiwa Chemical Industry Co., Ltd., product name: KP Plast Red 5B) was used.
[0121] Comparative Example 6 In preparing the coating solution for the charge transport layer, the amount of silica filler was changed to 3.30 g, the amount of tetrahydrofuran was changed to 29.7 g, and the dye CISolvent Red 52 (λ max A photoreceptor of Comparative Example 6 was prepared in the same manner as in Example 1, except that 0.40 g of KP Plast Red 5B (trade name: KP Plast Red 5B, manufactured by Kiwa Chemical Industry Co., Ltd., =540 nm) was used and the amount of tetrahydrofuran was changed to 102.30 g.
[0122] [evaluation] The photoreceptors produced in Examples 1 to 19 and Comparative Examples 1 to 6 were evaluated for the following items. For the following evaluations (1) and (2), each photoconductor was attached to a unit of a digital copying machine (manufactured by Sharp Corporation, model: MX-B455W) that had been modified for the test, and the evaluation was carried out.
[0123] (1) Light resistance The photoreceptor to be evaluated was exposed to 1000 Lux fluorescent light for 10 minutes and 400 Lux fluorescent light for 20 minutes, and the effect on the image after 1 minute was evaluated. The images in the exposed and unexposed areas were visually compared, and the light resistance was evaluated according to the following criteria. <Evaluation criteria> VG: No effect on image under both exposure conditions G: Slight image defects are observed when exposed to 1000 Lux, but there is no effect on the image when exposed to 400 Lux, so there is no problem. NB: Even with exposure to 400 Lux, slight image defects are observed, but this does not affect practical use. B: After exposure to light, clear image defects are observed.
[0124] (2) Recovery from light damage After carrying out the evaluation in (1) above, the photoconductor was left in a dark place for 10 minutes, and the effect on the image was evaluated in the same manner as in (1) above. The images in the exposed and unexposed areas were visually compared, and the light resistance (recovery from light damage) was evaluated according to the following criteria. <Evaluation criteria> VG: No effect on image under both exposure conditions G: When exposed to 1000 Lux, slight image defects are observed after 10 minutes in the dark, but when exposed to 400 Lux, there is no effect on the image after 10 minutes in the dark, so there is no problem. NB: Even with exposure to 400 Lux, slight image defects are observed after leaving the camera in the dark for 10 minutes, but this does not affect practical use. B: After exposure to light, clear image defects can be confirmed even after leaving the image in the dark for 10 minutes.
[0125] (3) Sensitivity stability The photoconductor to be evaluated was attached to the unit of a digital copier (Model: BP-40C26, manufactured by Sharp Corporation) that had been modified for the test, the developer was removed from the digital copier, and a surface potential meter (Model: MODEL 344, manufactured by Trek Japan) was attached to the development site instead. In an environment of 25°C temperature and 50% relative humidity, the initial residual potential and the surface potential of the photoconductor after electrical fatigue were measured, and the difference between these, ΔVr (V), was used to evaluate the sensitivity stability, which is an index of sensitivity deterioration due to repeated use, using the following evaluation criteria.
[0126] <Evaluation criteria> VG:ΔVr<40 Can be used without problems in high-speed multifunction machines or printers that require high sensitivity G: 40≦ΔVr<80 Can be used without problems on low to medium speed multifunction devices or printers NB:80≦ΔVr<140 If you have a slow, inexpensive multifunction device or printer, the density may be a little low, but it can be used without any problems. B:140≦ΔVr Poor sensitivity, low concentration, and problematic for practical use
[0127] (4) Printing durability The photoconductor to be evaluated was attached to the unit of a digital copier (model: BP-40C26, manufactured by Sharp Corporation) that had been modified for the test, and a developing unit was attached. The pressure at which the cleaning blade of the cleaning means contacted the photoconductor, the so-called cleaning blade pressure, was set to 21 gf / cm (2.05 × 10 -1A printing durability test was conducted by printing a character test chart (ISO19752) on 200,000 sheets of recording paper in an environment of 25°C temperature and 85% relative humidity. The thickness of the photosensitive layer at the start of the printing durability test and after 200,000 images were formed was measured using a film thickness measuring device (Filmetrics Inc., Model: F-20-EXR). The amount of film loss per 100,000 rotations of the photosensitive drum was calculated from the difference between the film thickness at the start of the printing durability test and the film thickness after 200,000 images were formed. The printing durability was evaluated based on the amount of film loss obtained according to the following criteria. The greater the amount of film loss, the worse the printing durability was evaluated to be.
[0128] <Evaluation criteria> VG: Film loss <0.50μm / 100,000 revolutions Can be used without problems in multifunction devices or printers that require a long lifespan G: 0.50μm / 100,000 revolutions≦film loss amount<0.70μm / 100,000 revolutions Although the amount of film loss is somewhat large, it can be used without any problems except for multifunction machines and printers that require a long life. NB: 0.70μm / 100,000 revolutions≦film loss amount<0.85μm / 100,000 revolutions Although there is a large amount of film loss, it can be used without problems on inexpensive multifunction devices and printers. B: 0.85μm / 100,000 revolutions or less film loss There is a lot of film loss, which is problematic for practical use.
[0129] [comprehensive evaluation] Based on the results of the above evaluations (1) to (4), if there was no "B" among the four items, the product was rated as "suitable for practical use," and if there was at least one "B" among the four items, the product was rated as "not suitable for practical use." Table 1 shows the main constituent materials used in the preparation of the photoreceptors of the Examples and Comparative Examples, their contents, and the relationship between them. Table 2 shows the evaluation results of the obtained photoreceptors. In Table 1, the silica fillers are represented by the alphanumeric characters of their product names or a part thereof, and the electron transport substances are represented by compounds 1-1 to 1-4.
[0130]
Table 1
[0131]
Table 2
[0132] From Tables 1 and 2, the following can be understood. (1) The photoconductors (Examples 1 to 19) having the constituent elements of the present disclosure are excellent in all of light resistance, recovery from light damage, sensitivity stability, and printing resistance. (2) When the relationship w / (d×x) of the content w of the silica filler, its average primary particle diameter d, and the content x of the electron transport material is 0.12 or less (Comparative Example 1), since w is too large with respect to (d×x), the potential stability deteriorates. On the other hand, when w / (d×x) exceeds 0.54 (Comparative Example 2), since w is too small with respect to (d×x) for the addition amount of the electron transport material with respect to the addition amount and average primary particle diameter of the silica filler, the desired light resistance and recovery from light damage cannot be obtained. (3) In Example 18, although it is not at a level that causes problems in actual use, deterioration of potential stability was observed. In Example 19, although it is not at a level that causes problems in actual use, weakness against light damage was observed. Therefore, a range of 0.12 < w / (x*d) < 0.54 is preferable.
[0133] (4) When the photosensitive layer does not contain a silica filler (Comparative Example 3), since the desired printing resistance cannot be obtained, the silica filler is an essential constituent element of the photosensitive layer. (5) When a dye having absorption of the light wavelength of a fluorescent lamp is added to the photosensitive layer instead of the electron transport material of the present disclosure, although a certain effect is observed with respect to light resistance due to the light shielding effect, no effect is observed with respect to recovery from light damage. When an amount that shows an effect on light resistance is added, sensitivity stability cannot be ensured (Comparative Example 5), and when the content of the dye is reduced to ensure a certain sensitivity stability, the light resistance deteriorates and problems in actual use occur (Comparative Example 6). Therefore, the electron transport material of the present disclosure is an essential constituent element of the photosensitive layer.
[0134] (6) Maximum absorption wavelength λ max Since the light resistance effect is reduced when an electron transport material with a small λ is used, it is necessary to select a material that sufficiently blocks wavelength components around 550 nm (Example 2). max Since the use of electron transport materials with large capacitance leads to poor sensitivity stability, it is necessary to select materials that do not block too much of the light wavelength component around 600 nm (Practical Step 3). (7) The same effect was obtained when using a material that has a good balance between blocking wavelengths around 500 nm and around 600 nm (Example 16), and the same effect was obtained even when the surface treatment of the silica was different (Example 17). [Explanation of symbols]
[0135] F01 Multilayer electrophotographic photoreceptor F1 Conductive support (support) F21 Undercoat layer (middle layer) F22 Charge generation layer F23 Charge transport layer Fa Photoconductor surface
[0136] 1 photoreceptor 31 Exposure means (semiconductor laser) 32 Charging means (charger) 33 Developing means (developer) 33a Developing roller 33b Casing 34 Transfer means (transfer charger) 35 Fixing means (fixing device) 35a Heating roller 35b Pressure roller 36 Cleaning means (cleaner) 36a cleaning blade 36b Recovery casing 37 Separation means 38 Housing 41, 42 arrow mark 44 Rotation axis 51 Recording media (recording paper or transfer paper) 100 Image forming apparatus (laser printer)
Claims
1. An electrophotographic photoreceptor having at least a photosensitive layer on a conductive support, The photosensitive layer comprises a silica filler and a compound represented by the general formula (I): 【Chemistry 1】 (In the formula, R a and R b are the same or different and each represents a hydrogen atom, a halogen atom, a cyano group, a nitro group, a hydroxyl group, an alkyl group having 1 to 12 carbon atoms, an alkoxy group having 1 to 12 carbon atoms, an aryl group which may have a substituent, a heterocyclic group which may have a substituent, an ester group, a cycloalkyl group, an aralkyl group which may have a substituent, an allyl group, an amide group, an amino group, an acyl group, an alkenyl group, an alkynyl group, a carboxyl group, a carbonyl group, a carboxylic acid group, or a halogenated alkyl group, and the substituent is a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, a hydroxyl group, a cyano group, an amino group, a nitro group, or a halogenated alkyl group. The electron transport material is represented by When the content of the silica filler relative to the total solid content of the photosensitive layer is w (mass%), the average primary particle diameter of the silica filler is d (nm), and the content of the electron transport material relative to the total solid content of the photosensitive layer is x (mass%), 0.12<w / (d×x)<0.54 The electrophotographic photoreceptor satisfies the relationship:
2. The electron transport material has a maximum absorption wavelength λ in the wavelength range of 515 to 560 nm. max The electrophotographic photoreceptor according to claim 1 ,
3. The electron transport material is a group represented by the substituent R b represents an aryl group which may have a substituent, and the substituent is a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, a hydroxyl group, a cyano group, an amino group, a nitro group, or a halogenated alkyl group.
4. The electron transport material is a group represented by the substituent R a and R b 4. The electrophotographic photoreceptor according to claim 3, wherein each of the is an aryl group which may have a substituent.
5. 3. The electrophotographic photoreceptor according to claim 1, wherein the photosensitive layer is a laminated type photosensitive layer having a charge generating layer containing a charge generating substance and a charge transport layer containing a charge transport substance.
6. 3. The electrophotographic photoreceptor according to claim 1, wherein a ratio w / d of a content w of the silica filler relative to the total solid content of the photosensitive layer to an average primary particle diameter d of the silica filler is in the range of 0.20 to 0.
95.
7. 3. The electrophotographic photoreceptor according to claim 1, wherein a ratio w / x of a content w of the silica filler relative to a total solid content of the photosensitive layer and a content x of the electron transport material relative to a total solid content of the photosensitive layer is in a range of 2.2 to 8.
0.
8. 3. The electrophotographic photoreceptor according to claim 1, wherein a value d×x obtained by multiplying an average primary particle diameter d of the silica filler and a content x of the electron transport material relative to the total solid content of the photosensitive layer is in the range of 20 to 110.
9. 3. The electrophotographic photoreceptor according to claim 1, wherein the silica filler is contained in an amount of 7 to 20% by mass based on the total solid content of the photosensitive layer.
10. 3. The electrophotographic photoreceptor according to claim 1, wherein the electron transport material is contained in an amount of 0.65 to 6.5% by mass based on the total solid content of the photosensitive layer.
11. 3. The electrophotographic photoreceptor according to claim 1, wherein the silica filler has an average primary particle size of 10 to 40 nm.
12. 3. A process cartridge comprising: the electrophotographic photosensitive member according to claim 1 or 2; and at least one selected from a charging unit that charges the electrophotographic photosensitive member, a developing unit that develops an electrostatic latent image formed by exposure to light to form a toner image, and a cleaning unit that removes toner remaining on the electrophotographic photosensitive member.
13. 3. An image forming apparatus comprising at least the electrophotographic photoreceptor according to claim 1 or 2, a charging unit which charges the electrophotographic photoreceptor, an exposure unit which exposes the charged electrophotographic photoreceptor to light to form an electrostatic latent image, a developing unit which develops the electrostatic latent image to form a toner image, and a transfer unit which transfers the toner image onto a recording medium.
Citation Information
Patent Citations
Electrophotographic photoreceptor, and process cartridge and image forming apparatus using the same
JP2010164639A
Electrophotographic photoreceptor, method for manufacturing same, and electrophotographic device using same
WO2018150693A1
